Transforming End-of-Life Care - Bok Yae Chung; Eun Hee Oh (Palliative Medicine and Hospice Care, 2016)
Currently, hospice care which focuses on caring for a terminally ill person delivers holistic, supportive, interdisciplinary, and patient-centered management. There have been nu-merous efforts to establish hospice care for people who are in the end-stage of their illness.